Spatial Analysis of Spill and Plant Biodiversity of Post-Impact Sites in Obio/Akpor LGA, Rivers State - Clifford, Anariochi, Bright; Wokekoro, Ogbumgbada, Emmanuel Chukwumene; Chike, Enyinda (American Journal of Biology and Natural Sciences, 2026)
Oil spills pose significant threats to plant biodiversity in Niger Delta regions. This study investigates the spatial distribution of oil spills and their impact on plant biodiversity in post-impact sites in Obio/Akpor LGA, Rivers State. This is against the background of the myriad of challenges/threats posed to its conservation for sustainable development. The study shows that the region is highly endowed with enormous biodiversity resources (both flora/fauna and also terrestrial/aquatic). Spatial analysis and field surveys reveal significant correlations between spill extent and plant species richness. Results show decreased plant diversity and altered community composition in impacted areas.